2022
DOI: 10.1038/s41415-021-3756-7
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID-19 pandemic on the mental health of dentists in Wales

Abstract: This study aimed to gain both an understanding of the impact that the COVID-19 pandemic has been having on the mental health of dentists working in Wales, as well as understanding the levels of stress the pandemic has caused. We also aimed to understand the specific causes of stress. The COVID-19 pandemic has had a large impact on dentistry across Wales and almost all aspects of the profession have been affected. Workloads have significantly changed, as well as the way patients can be treated. The pandemic has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
41
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 23 publications
6
41
0
8
Order By: Relevance
“…In addition, they also reported that having family members or relatives with suspected or confirmed COVID-19 was one of the risk factors for depression and stress. Regarding age, our findings agree with Owen et al 21 who indicated lower levels of stress in the 18–24 age group compared to other age groups. However, they differ with Nayak et al 43 who reported that those aged 30 years and younger had higher levels compared to the other age groups.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In addition, they also reported that having family members or relatives with suspected or confirmed COVID-19 was one of the risk factors for depression and stress. Regarding age, our findings agree with Owen et al 21 who indicated lower levels of stress in the 18–24 age group compared to other age groups. However, they differ with Nayak et al 43 who reported that those aged 30 years and younger had higher levels compared to the other age groups.…”
Section: Discussionsupporting
confidence: 92%
“…However, they differ with Nayak et al 43 who reported that those aged 30 years and younger had higher levels compared to the other age groups. This is probably because Nayak et al 43 conducted their study between May and June 2020 unlike Owen et al 21 and the present study which were conducted in 2021. The timing of the survey may have influenced the lack of resilience of younger people in this complex circumstance 48 and the lack of socialization 49 , 50 generating a greater psychological impact.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…The prevalence of burnout in dentists was another issue thoroughly investigated during the pandemic and found significant discrepancies. Dentists’ anxiety-related symptoms were, in general, aggravated, reaching in some cases more than 70% [ 14 ], their depression-related symptoms had overcome 60% [ 14 ], and stress was over 80% [ 14 , 26 , 27 ]. It was reported that only 27% of dentists announced significant depressive symptomatology [ 28 ], which makes us wonder about different factors influencing locally, ethnically, or culturing the phenomenon.…”
Section: Introductionmentioning
confidence: 99%